Misoprostol (Cytotec) for Prevention of Ovarian Hyperstimulation Syndrome. A Preliminary Investigation. - Leonardo Formigli; Rakotobe Andriamaro Andriantsirombaka; Ramarolahy Rija; Graziella Badulli; Hanitra Rasoarimanana; Nargis Ashurova; Ramachandran Krishnamoorthy (Journal of Fertility Biomarkers, 2019)
This preliminary study explores misoprostol as a preventive strategy for ovarian hyperstimulation syndrome. It outlines rationale, dosing considerations, and early safety signals, and calls for controlled trials to establish efficacy and risk–benefit.
Keywords: Ovarian Hyper Stimulation